Performance Management Practices and Productivity of Employees in the Ministry of Interior and Coordination of National Government, Kenya - OKELLO , JANE ACHUCHI; WAMWAYI, SCHOLASTICA WAMWAYI (Human Resource and Leadership Journal, 2022)
Purpose: The purpose of the study was to examine the influence of performance management practices on productivity of employees in the Ministry of Interior and Coordination of National Government, Kenya. Methodology: This study used descriptive research design to collect both qualitative and quantitative data. The target population of this study was 350 officers drawn from various departments. The study used simple random sampling techniques to select from the list of departments, directorates and divisions to be included in the study. This study adopted Yamane (1967) sampling formula to calculate the sample size which provided the number of responses that should to be obtained. Therefore, the sample size for this study was 187 employees. The respondents for this study constituted heads of departments in the Ministry. Findings: The study found that performance management practices significantly affect employee productivity in the Ministry of Interior and Coordination of National Government in Kenya. Unique Contribution to Theory, Policy and Practices: Based on the study findings, it was recommended that companies should encompass their training in all their activities in order to have competitive advantage. In addition, supervisors should oversee whether the work has been done appropriately in terms of procedures as it increases employee productivity. Furthermore, it was recommended that managers should attempt to minimize stress in organizations. The goals set by companies must be able to be broken into manageable simple actions achievable in the short term with the main focus on measurable, tangible results for each quarter.